Congenital abnormalities associated with Zika virus infection-Dengue as potential co-factor?: a systematic review - Petzold, Stephanie; Agbaria, Nisreen; Deckert, Andreas; Dambach, Peter; Winkler, Volker; Drexler, Jan Felix; Horstick, Olaf; Jänisch, Thomas (PLoS neglected tropical diseases, 2021)
Zika virus (ZIKV) emerged in Brazil during 2013-2014 causing an epidemic of previously unknown congenital abnormalities. The frequency of severe congenital abnormalities after maternal ZIKV infection revealed an unexplained geographic variability, especially between the Northeast and the rest of Brazil. Several reasons for this variability have been discussed. Prior immunity against Dengue virus (DENV) affecting ZIKV seems to be the most likely explanation. Here we summarise the current evidence regarding this prominent co-factor to potentially explain the geographic variability. This systematic review followed the PRISMA guidelines. The search was conducted up to May 15th, 2020, focussing on immunological interactions from Zika virus with previous Dengue virus infections as potential teratogenic effect for the foetus. Eight out of 339 screened studies reported on the association between ZIKV, prior DENV infection and microcephaly, mostly focusing on antibody-dependent enhancement (ADE) as potential pathomechanism. Prior DENV infection was associated with enhancement for ZIKV infection and increased neurovirulence in one included in vitro study only. Interestingly, the seven in vivo studies exhibited a heterogeneous picture with three studies showing a protective effect of prior DENV infections and others no effect at all. According to several studies, socio-economic factors are associated with increased risk for microcephaly. Very few studies addressed the question of unexplained variability of infection-related microcephaly. Many studies focussed on ADE as mechanism without measuring microcephaly as endpoint. Interestingly, three of the included studies reported a protective effect of prior DENV infection against microcephaly. This systematic review strengthens the hypothesis that immune priming after recent DENV infection is the crucial factor for determining protection or enhancement activity. It is of high importance that the currently ongoing prospective studies include a harmonised assessment of the potential candidate co-factors.
Gesehen am 11.02.2021